The Role of Technology Readiness and Perceptions in AI Adoption Among Accounting Students - Prabowo, Adia Adi (Universitas Islam Negeri Alauddin Makassar, 2024)
This study examines the impact of Technology Readiness, Digital Competence, Perceived Usefulness, and Perceived Ease of Use on the adoption of AI technology by accounting students at the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa. In the digital era, AI is increasingly utilized to facilitate human tasks, including those of students. However, some students are not yet prepared to adopt this technology, necessitating an evaluation of their readiness and perceptions. The study employs a quantitative method using Partial Least Square (PLS) analysis based on questionnaires distributed to 113 students. The results indicate that Optimism in Technology Readiness, Digital Competence, and Perceived Ease of Use significantly and positively influence AI adoption, while Perceived Usefulness does not show a significant effect. Keyword: Technology Readiness, Digital Competence, Perceived Usefulness, AI Adoption and Accounting Students.